2023
DOI: 10.32604/fdmp.2023.025681
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Plunger Lift Model for Shale Gas Wells

Abstract: At present, the optimization of the plunger mechanism is shale gas wells is mostly based on empirical methods, which lack a relevant rationale and often are not able to deal with the quick variations experienced by the production parameters of shale gas wells in comparison to conventional gas wells. In order to mitigate this issue, in the present work, a model is proposed to loosely couple the dynamics of gas inflow into shale gas wells with the dynamics of the liquid inflow. Starting from the flow law that ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Zhang Jinglong et al [20] used CFD technology to study the plunger liquid discharge mechanism and operation law and concluded that the overall operation time of the plunger can be estimated based on the average speed of the plunger. Miao Shiyu et al [21] established a kinetic model of plunger lifting to improve the average production of sample wells.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang Jinglong et al [20] used CFD technology to study the plunger liquid discharge mechanism and operation law and concluded that the overall operation time of the plunger can be estimated based on the average speed of the plunger. Miao Shiyu et al [21] established a kinetic model of plunger lifting to improve the average production of sample wells.…”
Section: Introductionmentioning
confidence: 99%